1992
DOI: 10.3354/meps080015
|View full text |Cite
|
Sign up to set email alerts
|

Land-based predator impact on vertically migrating zooplankton and micronekton advected to a Southern Ocean archipelago

Abstract: Combined acoustic (12 and 120 kHz) and trawling (RMT-2 and Bongo net) surveys in offshore waters of the Prince Edward Archipelago revealed diurnal vertical migration of major prey species (the euphausiid Euphausia vallentini and the myctophid fish Krefftichthys andersson~) of landbased predators. Migration was from 200-400 m in the day to near-surface levels at night and was linked to feeding periodicity. Consistently high winds result in drift of surface waters (down to 10-20 m) and advection of prey over the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(60 citation statements)
references
References 24 publications
3
57
0
Order By: Relevance
“…Seals and seabirds forage in diverse areas, often far from the PEIs, where they target frontal and bathymetric features at which their crustacean, fish and cephalopod prey are presumably concentrated (de Bruyn et al, 2009;Nel et al, 2001;Tosh et al, 2012). The shelf between the islands is somewhat enriched by topographic trapping of vertically migrating zooplankton and dense phytoplankton blooms (Perissinotto and Mcquaid, 1992) but the broad distribution pattern among seals and seabirds, however, reflects that macrozooplankton biomass over the inter-island shelf may be 3-8 times lower than in the offshore region. Also, adult mesopelagic fishes are virtually absent from the inter-island region, whereas they predominate the open waters of the Polar Frontal Zone (Mcquaid and Froneman, 2008;Pakhomov and Froneman, 1999;Pakhomov et al, 2000).…”
Section: Distribution In Relation To Foragingmentioning
confidence: 99%
“…Seals and seabirds forage in diverse areas, often far from the PEIs, where they target frontal and bathymetric features at which their crustacean, fish and cephalopod prey are presumably concentrated (de Bruyn et al, 2009;Nel et al, 2001;Tosh et al, 2012). The shelf between the islands is somewhat enriched by topographic trapping of vertically migrating zooplankton and dense phytoplankton blooms (Perissinotto and Mcquaid, 1992) but the broad distribution pattern among seals and seabirds, however, reflects that macrozooplankton biomass over the inter-island shelf may be 3-8 times lower than in the offshore region. Also, adult mesopelagic fishes are virtually absent from the inter-island region, whereas they predominate the open waters of the Polar Frontal Zone (Mcquaid and Froneman, 2008;Pakhomov and Froneman, 1999;Pakhomov et al, 2000).…”
Section: Distribution In Relation To Foragingmentioning
confidence: 99%
“…anderssoni form distinct schools in the Southern Ocean (Perissinotto and McQuaid, 1992;Zasel'sliy et al, 1985) and there is evidence from fish larval surveys that K. anderssoni also exhibit this behaviour around South Georgia (Belchier and Lawson, 2013). E. carlsbergi and K. anderssoni were found regularly in net samples at South Georgia during the timeframe of this study, but there was clear variation in their presence at the island between years (Collins et al 2008;Collins et al 2012; Figure 8).…”
Section: Possible Schooling Speciesmentioning
confidence: 95%
“…Myctophid schools, regardless of species or life cycle stage, were deeper and acoustically stronger in onshore regions where predation pressure from shore-based predators can be expected to be highest (Staniland et al, 2004). An acoustic study at Marion Island, Southern Ocean, reported an onshelf/offshelf gradient in the presence of a deep scattering layer (DSL) attributable to K. anderssoni whereby the DSL was strong in offshelf waters but faded gradually towards the island's shelf (Perissinotto and McQuaid, 1992). These authors suggested that increased predation pressure from land-based predators in the inshore regions was responsible for this trend.…”
Section: Insight Into Myctophid Ecologymentioning
confidence: 98%
See 1 more Smart Citation
“…When there are few krill, the condition of mackerel icefish is negatively affected and growth rates are reduced (Everson et al, 1997(Everson et al, , 1999. In sub-Antarctic regions, Antarctic krill are less important, and the advection of zooplankton and myctophid fish into shelf areas helps maintain local food webs (Perissinotto and McQuaid, 1992;Pakhomov and Froneman, 1999b).…”
Section: Impacts Of Advection On Fish Populations In the Antarcticmentioning
confidence: 99%